2022
DOI: 10.15562/ijbs.v16i2.426
|View full text |Cite
|
Sign up to set email alerts
|

Identification of active chemical compounds and potential antibacterial snail mucus (Achatina fulica) on bacteria Enterococcus foecalis causes of periodontitis

Abstract: Background: A chemical compound is a chemical compound present in a natural source that gives it the special properties and characteristics of the plant or animal source. Snail slime is one of the traditional medicines from animals that is used by the community as a traditional medicine for healing minor wounds and toothaches. The aim of this study was to identify the active chemical compounds and antibacterial potential of snail mucus against the bacteria E. foecalis that causes periodontitis. Method: True ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…The cysteine-rich antimicrobial peptide Mytimacin-AF isolated from A. fulica mucus showed potent antimicrobial activity against a wide range of bacteria (with the strongest antimicrobial activity against S. aureus ) and the fungus Candida albicans . Further chemical analyses identified antimicrobial metabolites, including glycosaminoglycans, achasin, acharan sulfate, and beta-agglutinin, exhibiting potent antibacterial effects against Enterococcus foecalis , one of the bacteria responsible for causing periodontitis . Bioactive compounds extracted from H. aspersa soft tissue demonstrated strong antifungal effects against C. albicans , Aspergillus flavus , and Aspergillus brasiliensis .…”
Section: Multifunctional Biomaterials With Diverse Biomedical and Cos...mentioning
confidence: 99%
See 1 more Smart Citation
“…The cysteine-rich antimicrobial peptide Mytimacin-AF isolated from A. fulica mucus showed potent antimicrobial activity against a wide range of bacteria (with the strongest antimicrobial activity against S. aureus ) and the fungus Candida albicans . Further chemical analyses identified antimicrobial metabolites, including glycosaminoglycans, achasin, acharan sulfate, and beta-agglutinin, exhibiting potent antibacterial effects against Enterococcus foecalis , one of the bacteria responsible for causing periodontitis . Bioactive compounds extracted from H. aspersa soft tissue demonstrated strong antifungal effects against C. albicans , Aspergillus flavus , and Aspergillus brasiliensis .…”
Section: Multifunctional Biomaterials With Diverse Biomedical and Cos...mentioning
confidence: 99%
“…53 Further chemical analyses identified antimicrobial metabolites, including glycosaminoglycans, achasin, acharan sulfate, and beta-agglutinin, exhibiting potent antibacterial effects against Enterococcus foecalis, one of the bacteria responsible for causing periodontitis. 54 Bioactive compounds extracted from H. aspersa soft tissue demonstrated strong antifungal effects against C. albicans, Aspergillus f lavus, and Aspergillus brasiliensis. 55 Liquid chromatography−mass spectrometry identified metabolites, including flavonoids, fatty acids, and steroids, as antifungal agents within the snail extracts.…”
Section: Multifunctional Biomaterials With Diverse Biomedical and Cos...mentioning
confidence: 99%
“…Inhibition of falcipain-2 function causes the accumulation of nondegradable hemoglobin in food vacuoles [25]. In vivo study found that flavonoids are easily transformed into radical anions under a cellular oxidative stress environment, which severely induces the destruction of proteins, RNA, and DNA [30].…”
Section: Evaluation Of Inhibition Rate Percentage and Ic50mentioning
confidence: 99%